Modulation of Tumor Vasculature Network: Key Strategies. Issue 6 (29th March 2022) - Taleb, Mohammad; Mohammadkhani, Niloufar; Bahreini, Farbod; Ovais, Muhammad; Nie, Guangjun
Abstract : Tumor cells, owing to their relentless division, require increased nutrient supply. This is made possible by angiogenesis, that is, the formation of new blood vessels increases the blood flow toward tumor cells, thereby promoting the supply of oxygen and vital nutrients required for the proliferation of tumor cells. Decreasing the blood flow to the tumor cells can effectively halt tumor progression and possibly cure cancer. However, practically, the mechanism is not as straightforward as it seems. In this review, the role of angiogenesis is focused on in the development of tumors and cancer metastasis and the potential of tumor vascular normalization for the reduction of angiogenesis, which results in the suppression of tumor cells. An insight into various strategies, including pharmacological inhibition of angiogenesis, genetic models, and nanoparticle‐based novel treatment strategies for vascular normalization, is provided. In addition, the effect of vessel normalization and tumor microenvironment modulation on the delivery of nanoparticle‐based drugs to the target tumor cells is discussed. The critical role of monitoring vascular normalization is also highlighted, without which selecting the most efficient strategy for tumor vascular normalization is possible. Therefore, efficiently combating cancer and its devastating effects remains an unsolved puzzle. Abstract : For a proper diagnosis and treatment of cancer, it is crucial to understand cancer biology. Supply of blood is necessary for tumor cells to grow, which is made possible by angiogenesis. Tumor cells need a greater supply of blood to grow. Studies of changes in the morphology of blood vessels during angiogenesis can be used to detect tumor formation.